The Public Perception of The Development of River of Life Area as A Tourist Attraction in Kuala Lumpur - Fitri, Melisa Rona; Harmainis, Nurasyiqin Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to determine the public's perception of the development of the River of Life area as a tourist attraction in Kuala Lumpur. This type of research is descriptive qualitative research that uses observation, interviews and documentation as data collection instruments. Sampling Technique using Accidental Sampling technique. While the data source consists of primary data obtained directly in research in the field. The results of this study found: 1) Public perception of the development of the River of Life area as one of the tourist attractions in Kuala Lumpur is very good. Because, Rifer of Life revitalizes the old environment, increases the historic attractiveness of the city, provides an effective transformation network to ensure a pleasant journey for residents and tourists. 2) Public perception of access to River of Life is very good. 3) Community perception with the development of the River of Life area is very good because it can open up new opportunities and jobs for the local community. River of Life provides affordable housing for more than 35,000 new residents, one million square meters of commercial space, more than 27,000 new job opportunities, increased using of public transportation. 4) Community perception of the uniqueness of the River of Life area as a tourist attraction is that there is one component of the River of Life project, namely the Blue Pool or Blue Poll which is the River Beautification Project located next to the Sultan Abdul Samad Building.